Bacteriophage Therapy: Developments and Directions - Mikeljon P. Nikolich; Andrey A. Filippov (MDPI AG, 2020)
In an era of proliferating multidrug resistant bacterial infections that are exhausting the capacity of existing chemical antibiotics and in which the development of new antibiotics is significantly rarer, Western medicine must seek additional therapeutic options that can be employed to treat these infections. Among the potential antibacterial solutions are bacteriophage therapeutics, which possess very different properties from broad spectrum antibiotics that are currently the standard of care, and which can be used in combination with them and often provide synergies. In this review we summarize the state of the development of bacteriophage therapeutics and discuss potential paths to the implementation of phage therapies in contemporary medicine, focused on fixed phage cocktail therapeutics since these are likely to be the first bacteriophage products licensed for broad use in Western countries.